Oxygen Uptake Rate Controlling Strategy Balanced with Oxygen Supply for Improving Coenzyme Q10 Production by Rhodobacter sphaeroides - Wang, Ze-Jian; Zhang, Xingzi; Wang, Ping; Sui, Zhiwei; Guo, Meijin; Zhang, Siliang; Zhuang, Yingping (Biotechnology and bioprocess engineering, 2020)
The effects of different oxygen uptake rates (OUR) on the physiological metabolism of Rhodobacter sphaeroides were investigated systematically in 50 L fermenters due to the significant influence on industrial coenzyme Q10 production under oxygen supply limitation. Meanwhile, the seriously decreased oxygen transfer rate caused by the increased broth viscosity was successfully prevented with OUR-directed continuous ammonium sulfate feeding in the late fermentation phase. The statistical analysis results showed that controlling OUR constantly at 45 ± 2.2 mmol/L/h by the oxygen supply level adjustment and the continuous ammonium sulfate feeding could greatly enhance Q 10 production. This OUR-Stat controlling strategy successfully achieved the maximal coenzyme Q 10 production (2584 ± 82 mg/L), which was 15.4% higher than that of the control. The highest specific CoQ 10 content was 25.9 mg/(g DCW)), and the yield of CoQ 10 to glucose consumption was up to 19.37 mg/g. These results demonstrated that the optimal OUR-Stat controlling strategy would be effective and economical for improving the industrial CoQ 10 production.